2012
DOI: 10.1080/03634523.2011.620617
|View full text |Cite
|
Sign up to set email alerts
|

“If You Can Dream It, You Can Achieve It.” Parent Memorable Messages as Indicators of College Student Success

Abstract: This study investigated various aspects of parents' memorable messages about college as they relate to indicators of college student success. Findings revealed that parents' memorable messages about college focused on working (and playing) hard, the necessity of attending college, providing encouragement and support, and general advice based on parents' own experiences. Although these message themes were not uniquely predictive of college student success, the students' perceptions of message and sender charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 56 publications
(107 reference statements)
7
20
0
Order By: Relevance
“…A healthy family situation can be one of the strongest factors in promoting resiliency (Kranstuber, Carr, & Hosek, 2012). Emerging adults with experience in the foster system often lack the stability and security provided to many by their birth parents, as they are bounced around from home to home, unable to form proper attachments, and are exposed to additional risk factors.…”
Section: Purpose and Importancementioning
confidence: 99%
See 3 more Smart Citations
“…A healthy family situation can be one of the strongest factors in promoting resiliency (Kranstuber, Carr, & Hosek, 2012). Emerging adults with experience in the foster system often lack the stability and security provided to many by their birth parents, as they are bounced around from home to home, unable to form proper attachments, and are exposed to additional risk factors.…”
Section: Purpose and Importancementioning
confidence: 99%
“…A child-focused perspective is not an unjustified approach, but such legislation can completely circumvent the importance of family. A positive relationship with family members can lead to increased resiliency, greater life satisfaction, and overall higher levels of wellbeing, and most of these behaviors are found in the everyday practices of families (Benzies & Mychasiuk, 2009;Courtney et al, 2012;Kranstuber et al, 2012;Masten, 2001). With such a strong potential to positively influence development, requiring little more than "ordinary magic", foster families simply should not be overlooked (Masten, 2001).…”
Section: Purpose and Importancementioning
confidence: 99%
See 2 more Smart Citations
“…Memorable messages have been used as a unit of communication analysis in a plethora of contexts. Examples are gender socialization of new university faculty (e.g., Dallimore, 2003), organizational newcomer socialization (e.g., Barge & Sclueter, 2004;Stohl, 1986), volunteerism with nonprofit organization (e.g., Steimel, 2013), perceptions about aging (e.g., Fung & Carstensen, 2003;Holladay, 2002), constructions of the sense of who one is as an individual (Heisler & Ellis, 2008); college life (e.g., Dunleavy & Yang, 2015;Kranstuber, Carr, & Hosek, 2012;Wang, 2012), nurses' support messages (Ford & Ellis, 1998), illness and healthcare (e.g., Cooke-Jackson, Orbe, Johnson, & Kauffman, 2014;Lauckner et al, 2012;Smith et al, 2010), sports socialization (e.g., Colon, 2011;Cranmer, 2015;Kassing & Pappas, 2007;Starcher, 2015;), end-of-life conversations about religious faith (e.g., Keeley, 2004), and-particularly useful and similar to this study-family and work (Medved, Brogan, McClanahan, Morris, & Shepherd, 2006). found that men and women received similar messages about the role that family should play in their lives; however, women were more frequently encouraged toward selecting work that would allow them to prioritize family needs, and were also advised to exit the workforce after the birth of a child.…”
Section: Memorable Messagesmentioning
confidence: 99%